2018
DOI: 10.14474/ptrs.2018.7.1.13
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between the physical power of golf players and the Titleist Performance Institute Level 1 test

Abstract: Objective: This was a correlation study for predicting the power to improve the distance of golf players and developing an effective power program. Design: Cross-sectional study. Methods: The subjects of this study were 24 healthy males and females in their 20s and 30s who were golf athletes living in Seoul and Gyeonggi-do. In the Titleist Performance Institute (TPI) Level 1 test, the twelve swing characteristics include components of stability, mobility, body conditioning ability, and balance. The power test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The athletes seated on the floor in an extended-legs position (feet 60 cm apart) while their back was in touch with the wall. The medicine ball (4 kg for men and 2 kg for women) was held with both hands in front of the chest with the forearms parallel to the ground (Kim, Jongeun, & Kwangsun, 2018;Salonia, Chu, Cheifetz, & Freidhoff, 2004). While their back part was touching the wall, participants threw the medicine ball straight forward as strongly and as far as they could.…”
Section: Performance Testsmentioning
confidence: 99%
“…The athletes seated on the floor in an extended-legs position (feet 60 cm apart) while their back was in touch with the wall. The medicine ball (4 kg for men and 2 kg for women) was held with both hands in front of the chest with the forearms parallel to the ground (Kim, Jongeun, & Kwangsun, 2018;Salonia, Chu, Cheifetz, & Freidhoff, 2004). While their back part was touching the wall, participants threw the medicine ball straight forward as strongly and as far as they could.…”
Section: Performance Testsmentioning
confidence: 99%
“…The athletes were seated on the floor with extended legs, feet 60 cm apart and the back against a wall. The medicine ball (4 kg men and 2 kg women) (18,19), was held with both hands on the side and a little behind center and back against chest. Forearms were located parallel to the floor.…”
Section: Seated Chest Pass Testmentioning
confidence: 99%
“…To date, 3 studies have attempted to assess the "golf specific functional movement screening tests" with only 2 assessing the relationship to swing faults (18,20,38). Gulgin et al (18) and Speariett and Armstrong (38) reported that of those who presented a limited OHS, 54 and 90%, respectively, exhibited loss of posture in the backswing and that 67 and 60%, respectively, showed a degree of early hip extension in the downswing.…”
Section: Introductionmentioning
confidence: 99%